Prenatal Substance Exposure and Developmental Trajectories of Internalizing Symptoms: Toddlerhood to Preadolescence. (1st January 2021) - Min, Meeyoung O.; Albert, Jeffrey M.; Lorincz-Comi, Noah; Minnes, Sonia; Lester, Barry; Momotaz, Hasina; Powers, Gregory; Yoon, Dalhee; Singer, Lynn T.
Highlights: Prenatal substance exposure (PSE) impedes fetal brain development. Five trajectories of internalizing behavior were identified in both boys and girls. Prenatal tobacco exposure and postnatal maternal drinking were related to risky trajectories. The no risk trajectory was represented by more boys; the chronic risk trajectory by more girls. Abstract: Background: Little is known about how prenatal exposure to substances (alcohol, tobacco, marijuana, and cocaine) may contribute to heterogeneous childhood trajectories of internalizing symptoms (i.e., depression, withdrawal, anxiety). The present study aimed to identify developmental trajectories of internalizing symptoms in children using gender-separate analyses and to examine whether trajectories differ by prenatal substance exposure (PSE) and other environmental and biological correlates. Methods: Data from two large community-based birth cohorts with PSE were integrated ( N = 1, 651, 848 boys, 803 girls): the Cleveland cohort and the Maternal Lifestyle Study (MLS). Internalizing symptoms were assessed with the Child Behavior Checklist at ages 2, 4, 6, 9, 10, 11, and 12 in the Cleveland study and at ages 3, 5, 7, 9, 11, and 13 in the MLS. Results: Gender-separate group-based trajectory modeling yielded five distinctive developmental trajectories of internalizing symptoms from ages 2 to 13 in both boys and girls: low-risk group (14.4% girls, 28.8% boys); normative-decreasing group (35.3% girls, 33.1% boys); increasing risk group (14.4% girls, 13.0% boys); early-high group (22.3% girls, 17.9% boys); and chronic group (13.8% girls, 7.2% boys). Prenatal tobacco exposure, maternal psychological distress, and postnatal maternal alcohol use differentiated the longitudinal courses of internalizing symptoms. Boys were more likely to follow the low-risk trajectory, whereas girls were more likely to follow the chronic trajectory. Conclusions: Prenatal tobacco exposure was associated with suboptimal developmental trajectories of internalizing symptoms in the context of prenatal poly-drug exposure, highlighting a need for continued and increased effort toward prevention of prenatal tobacco use.